HIBRIDISASI BUATAN Melaleuca alternatifolia DENGAN JENIS TERDEKAT : M. dissitiflora dan M. linariifolia - Liliana Baskorowati (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2008)
Melaleuca alternifolia (tea tree) is one of Australian species for oil production purpose. Breeding strategies to improve the oil quality has been established since 1998, amongs them is artificial hybridisation between M. alternifolia with its close relatives of M. linariifiolia and M. dissitiflora. This study therefore aimed to produce hybrids of M. alternifolia x M. linariifolia and M. alternifolia x M. dissitiflora. These hybrids are expected to have oil with chemotypes meeting the standard requirements and to improve adaptability to drought environment. Two methods being used in this study were: conventional controlled pollination and one stop pollination. The results showed that both pollination methods successfully produce hybrid of M. alternifolia x M. dissitiflora. The number of capsule produced from conventional controlled pollination was much higher than from one stop pollination. Hybrids seedlings at 3 months old showed intermediate morphological characteristics of the parental seedlings.